PENGARUH KARAKTERISTIK TATA KELOLA PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN EMISI KARBON - Purnayudha, Nisrina Azmi; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2022)
The study tested the role of good corporate governance and enviromental performance to carbon emissons disclosure in companies listed on the Indonesia Stock Exchange (IDX) of 2015 until 2019. The data used was 248 company. The testing of hypotheses using ordinary least square regression. On the other side, the f shows a model that is stable and significant. R-square is 13,63%, showing no other variables that can affect a model of 86,37%. The result of this research shows it has three variables without significant impact on carbon emissions disclosure is, board size, foreign diversity and age firms. On the other hand this research has live variable significant that is, independent commissioner and director, enviromental performance, size firms and leverage. This outcome support previous studiesÂ KÄ±lÄ±c dan Kuzey (2019); Nasih et al., (2019); Setiawan dan Iswati (2019).